Mechanical stiffening of porphyrin nanorings through supramolecular columnar stacking - Svatek, Simon A.; Perdigão, Luis M.A.; Stannard, Andrew; Wieland, Maria B.; Kondratuk, Dmitry V.; Anderson, Harry L.; O'Shea, James N.; Beton, Peter H. (American Chemical Society, 2013)
Solvent-induced aggregates of nanoring cyclic polymers may be transferred by electrospray deposition to a surface where they adsorb as threedimensional columnar stacks. The observed stack height varies from single rings to four stacked rings with a layer spacing of 0.32 ± 0.04 nm as measured using scanning tunneling microscopy. The flexibility of the nanorings results in distortions from a circular shape, and we show, through a comparison with Monte Carlo simulations, that the bending stiffness increases linearly with the stack height. Our results show that noncovalent interactions may be used to control the shape and mechanical properties of artificial macromolecular aggregates offering a new route to solvent-induced control of two-dimensional supramolecular organization.